(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Rock failures are a very frequent phenomenon, especially on slopes that cut off roads in mountainous areas. The road leading to the village of Al-Naml, which is located north of Tikrit City, is considered the most important road that connects this village to the neighboring areas and cities. This road sometimes experiences several rock failures that cause difficulty in transportation for people, especially in winter and spring. Therefore, evaluating the stability of rocky slopes on such a road is very necessary. Four slope stations are selected along this road to evaluate the stability of rocky slopes using different techniques. The selection of slope stations is based on the difference in the pattern of discontinuities, the change in the morphology of the slope, and the difference in the type of failures. The failure that occurred in the area is a rockfall, while the expected one is direct toppling. The information taken from the field has been analyzed to determine the degree of stability probability through engineering analysis (Kinematic analysis) using the DIPS-v6.008 program, as well as through the system of giving values ​​to the slope mass rating (SMR) using the SMRTool-V205 program. The engineering analysis (kinematic analysis) showed that wedge sliding is possible at all stations (1,2,3,4), while plane sliding, flexural, toppling, and direct toppling are not likely to occur. The values of SMR for both Discrete-SMR and Continuous-SMR for the slopes of all stations range from (37-1) and (37-5), respectively. It is observed that the values at stations (1,2,3) are within a completely unstable range with a probability of failures of about (0.9), while the value at station (4) is within the unstable range with a probability of failure of about (0.6).